Pertanggungjawaban Dalam Penerapan Asas Itikad Baik Pada Transaksi Online Sebagai Upaya Perlindungan Konsumen - Merlinda Tri Purwani; Suraji Suraji (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The development of increasingly sophisticated technology has resulted in changes in the use of internet networks used for online buying and selling ore-commerce. This research aims to determine the importance of implementing the principle of good faith in online buying and selling agreements as a responsibility for losses experienced by consumers in online transactions as an effort to protect consumers. The principle of good faith is an important principle, good faith must be exercised by sellers in order to provide protection to consumers, in order to minimize violations of consumer rights.